1998
DOI: 10.1001/archotol.124.10.1090
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of Endoscopic Surgery for Frontal Sinusitis

Abstract: Although the long-term results of endoscopic surgery for frontal sinusitis are unknown, this approach appears to be effective for most patients and may provide a reasonable alternative to frontal sinus obliteration surgery in selected cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 17 publications
1
63
0
2
Order By: Relevance
“…It could be verified that endonasal sinus surgery reduces nasal impairments of CRS patients [6,13,37,47]. Another study with this questionnaire dealing with cost-benefit analysis after endonasal sinus surgery revealed that the treatment of mild forms of CRS is more cost-effective when compared with the treatment of pansinusitis [49].…”
Section: Chronic Sinusitis Survey (Css)mentioning
confidence: 81%
See 1 more Smart Citation
“…It could be verified that endonasal sinus surgery reduces nasal impairments of CRS patients [6,13,37,47]. Another study with this questionnaire dealing with cost-benefit analysis after endonasal sinus surgery revealed that the treatment of mild forms of CRS is more cost-effective when compared with the treatment of pansinusitis [49].…”
Section: Chronic Sinusitis Survey (Css)mentioning
confidence: 81%
“…In 1996, the healthcare expenditures for sinusitis in the US were 5.8 billion Dollars [5]. Gliklich and Metson [6] performed a break-even analysis and calculated a time period of 7 years until amortization of treatment costs can be achieved by reduced postoperative use of resources.…”
Section: Introductionmentioning
confidence: 99%
“…Experiences in endoscopic surgery for frontal sinusitis and orbital decompression have added significantly to the progress in minimally invasive cranial base surgery. 29,30,37,49 Once considered an adjunct to microsurgical techniques, the EEEA now has become an evolving alternative in many centers in achieving resection through a smaller corridor to decrease patient morbidity. Kassam et al described some of the advantages of the EEEA in comparison with traditional transcranial approaches include reduction in the extent of bone resection, elimination of brain retraction, and less manipulation of neu rovascular structures.…”
Section: 44mentioning
confidence: 99%
“…The Philadelphia group found in their series of 130 frontal sinusotomies that 10 (8%) required further intervention based on endoscopic findings and the ability to cannulate the frontal sinus [14]. Other centres have also reported excellent results using similar endoscopic techniques [3,15] and have been able to demonstrate a significant improvement in the quality of life of the patients post-operatively [16]. Maintaining the theme of the minimally invasive approach, the frontal sinus rescue procedure is an alternative option to employ when the middle turbinate has been previously resected [17,18].…”
Section: Endoscopic Frontal Sinusotomymentioning
confidence: 99%